Battle of the sexes (2017) [videorecording (DVD)] - Stone, Emma, 1988-; Carell, Steve, 1962-; Silverman, Sarah; Pullman, Bill; Cumming, Alan, 1965-; Shue, Elisabeth (Twentieth Century Fox Home Entertainment, 2017)
In the wake of the sexual revolution and the rise of the women's movement, the 1973 tennis match between women's world champion Billie Jean King and ex-men's-champ and serial hustler Bobby Riggs became one of the most watched televised sports events of all time, reaching 90 million viewers around the world. As the rivalry between King and Riggs kicked into high gear, off-court each was fighting more personal and complex battles.